Démarches environnementales volontaires, conflit d’usage et proximité - Marie-Claude Bélis-Bergouignan; Clarisse Cazals (Développement Durable et Territoires)
This paper analyses, terms of geographical and organized proximity, the contribution of Voluntary Environmental Approaches (VEA) to the resolution of diffuse conflicting water uses in vine growing and fruit-bearing arboriculture. In a first part, we show that VEAs are a specific producer’s response to this kind of conflicts, the second part being centred on an analysis of VEAs in terms of proximity. An investigation towards producers engaged in integrated or organic farming shows that organized proximity alone is not able to bear solutions to divergences of interests between actors.